(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Early child labor has been and is a prominent issue that needs to be improved and pushed back all over the world. Currently, the situation of children working early, especially in heavy, dangerous, and hazardous jobs will significantly affect the physical, mental and cognitive development of children. The article deals with the current situation and outlines the individual social work process to support and prevent early child labor.